The Effect Of Physical Activity To Reduce Blood Glucose Levels In Patients With Type 2 Diabetes Mellitus (Literature Review) - Yunita Ega Safitri; Dewi Rachmawati; Wiwin Martiningsih (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2022)
Physical activity is very important for people with diabetes mellitus because it is associated with the speed of recovery of muscle blood sugar. The purpose of the literature is to determine the effect of physical activity in reducing blood glucose levels in patients with type 2 diabetes mellitus. The method used is a traditional review with the sample being accredited national journals, with inclusion criteria, national and international journals from different databases and related variables, with The research design was quasi-experimental and cross-sectional, a journal published in 2010-2020. The results showed that physical activity was carried out, prolanis exercise, brisk walking for 30 minutes, light walking for 30 minutes, fitness for the elderly, the results of blood sugar levels before doing physical activity had the lowest average value of 108 mg/dl and the average value the highest is 248 mg/dl, blood sugar levels after physical activity have the lowest average value of 102 mg/dl and the highest average value is 187 mg/dl, there is an effect of prolanis exercise, brisk walking for 30 minutes, light walking 30 minutes, elderly fitness exercise on decreasing blood sugar levels with p values ??in a row: p=0.027, p=0.002, p=0.000, p=0.000. Physical activity can significantly reduce blood glucose levels if it is done regularly, structured and continuously in an appropriate time.